Batteries and beyond: Multi-vector energy storage as a tool to decarbonise energy services - Greening, Benjamin; Braunholtz-Speight, Tim; Wood, Ruth; Freer, Muir (Frontiers in Energy Research, 2023)
With the 2015 Paris Agreement pursuing efforts to limit global temperature increase to below 2 degrees Celsius above pre-industrial levels and the ‘energy trilemma’ goals of energy security, energy equity and environmental sustainability, decarbonisation remains a priority across all of the United Kingdom (UK) energy system, not just electricity. Electricity and thermal energy storage technologies can offer a host of benefits across the energy value chain through the ability to capture, store and then release electricity or thermal energy over a period of time. These benefits include helping capture the full potential of renewable generation and providing services such as frequency response and reserve to Great Britain’s (GB) electricity system. In addition, with the aforementioned climate targets in mind, energy storage can also play a role in facilitating the decarbonisation of other activities and sectors. Here we delve deeper into how energy storage technologies can contribute to both energy sector transformation and more broadly, decarbonisation. Furthermore, we discuss the importance of ensuring a technology-agnostic approach to the development of policy and regulation with relevance to energy storage. This ensures that storage technologies with significant potential to contribute to the ‘energy trilemma’ goals are not precluded from entering the market due to unfavourable policy and regulatory frameworks.